2018
DOI: 10.1101/242149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study of 1 million people identifies 111 loci for atrial fibrillation

Abstract: SummaryTo understand the genetic variation underlying atrial fibrillation (AF), the most common cardiac arrhythmia, we performed a genome-wide association study (GWAS) of > 1 million people, including 60,620 AF cases and 970,216 controls. We identified 163 independent risk variants at 111 loci and prioritized 165 candidate genes likely to be involved in AF. Many of the identified risk variants fall near genes where more deleterious mutations have been reported to cause serious heart defects in humans or mic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…In recent pre-publication results, Nielsen et al, reported 111 loci from 60,620 AF cases and more than 970,000 referents, 15 including more than 18,000 AF cases from our prior report. 8 We therefore performed a preliminary meta-analysis for the top loci in nonoverlapping participants from these two large efforts with a resulting total of over 93,000 AF cases and more than 1 million referents.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…In recent pre-publication results, Nielsen et al, reported 111 loci from 60,620 AF cases and more than 970,000 referents, 15 including more than 18,000 AF cases from our prior report. 8 We therefore performed a preliminary meta-analysis for the top loci in nonoverlapping participants from these two large efforts with a resulting total of over 93,000 AF cases and more than 1 million referents.…”
mentioning
confidence: 54%
“…We meta-analyzed 111 variants from externally reported 15 provisional loci within predominantly non-overlapping samples from the Broad AF Study, BBJ, EGCUT, PHB, SiGN and the Vanderbilt AF Registry with METAL (released on 2011–03-25). 52 The predominantly nonoverlapping samples included a total of 32,957 AF cases and 83,546 referents, with minimal overlap from the studies MGH AF, BBJ and AFLMU.…”
Section: Methodsmentioning
confidence: 99%
“…In our MR analyses using methods robust to the inclusion of invalid 33 . However, the effect estimates of heart rate reduction on atrial fibrillation are similar when using the GWAS results from Nielsen et al which include both population-based and clinical cohorts 12 . The possibility that the effect is greater in healthy patients is also supported by the previously described association between low heart rate during physical activity and the increased incidence of atrial fibrillation 34 .…”
Section: Effect Of Hcn4 On Atrial Fibrillationmentioning
confidence: 80%
“…We used hospitalization data between GRCh37. We also used the largest available meta-analysis of genome-wide association studies (GWAS) with summary statistics reporting the effect of the HCN4 rs8038766 variant on stroke, atrial fibrillation, CAD, myocardial infarction and heart failure (Supplementary methods) [10][11][12][13][14] .…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation